Passive Smoking Also Affects Recovery from Anaesthesia - Erhan, Omer Lutfi; Ileri, Abdurrahman; Bulut, Oguz Kagan; Ozer, Ayse Belin (Aves, 2017)
[Abstract Not Available]
Pasif sigara İçiciliği anesteziden derlenmeyi de etkiler
Keywords: Environmental Tobacco-Smoke; Children